Why do children in Singapore read? An exploratory study - Kusolpalin, Pattarin; Luyt, Brendan; Lynda Munro, Yasmin; Lim, Sieu Pin (Malaysian Journal of Library and Information Science, 2017)
Kusolpalin, P., Luyt, B., Munro, Y. L., & Lim, S. P. (2013). Why do children in Singapore read? An exploratory study.Â Malaysian Journal of Library & Information Science,Â Vol.18, no. 3: 1-12. The study aims to find out why Singaporean children read, as well as the role and benefit reading plays in their lives. It also probes into their motivation for reading and how they choose books. Thirty children were interviewed and the findings of several previous studies confirmed. A significant new finding was that although children are aware of the benefits and pragmatic reasons of reading, they read for their own satisfaction, and any benefit they reap is incidental and not intentional. Recommendations to improve library services for children are made at the end.